Populism on the Web: Presidential Elections in Bolivia, Ecuador, Peru, and Colombia (2020–2022) - Maria-Ines Quevedo-Stuva; Gloria Tovar-Gil; Andrea Mila-Maldonado (Societies, 2023)
Populism has become one of the main features of political action worldwide. This research aims to characterize the populist discourse in the tweets of presidential candidates in the Andean Community in recent elections (2020–2022). Accordingly, we analyze the characteristics of their social network profiles, as well as the content and latent discourse of their tweets. We demonstrate that the differences and similarities of their discourse go beyond their right and left association. The differences result from how they construct their identity and establish their relationship with their electorate. Our analysis reveals that this type of discourse is ideological as well as performative. It is ideological because, in the candidates’ discourse, they recontextualize the actual meanings of “us” and “them”. It is performative because it is carried out by a charismatic leader who acts in a specific way to define himself or herself as the embodiment of “the people” and “the good”.